Fish and Invertebrate Yields of the Coral Reefs of Selinog Island in the Mindanao Sea and Hulao-hulao in Panay,Gulf, Philippines - Luchavez, Teodulo; Luchavez, Julieta; Alcala, Angel C. (Silliman Journal, 2024)
The fish and invertebrates caughi ai the reefs of Selinog Island in the Mindanao Sea and Hulao-hulao in Panay Gulf were studied from April 1982 to August 1984. The fish and invertebrate yield of Selinog was estimated at 5.88 m t/yr/sq km and that of Hulao-hulao at 5.0.m t/yr/sq km. In addition to reef fishes, the harvest included fishes of the families Carangidae, Belonidae, Scombridae, Sohyraenidae and some cartilaginous fishes such as rays and sharks. Selinog reef has an area of about 126.3 ha, while Hulao-hulao reef is about 50 ha. Both reefs have been dynamited and subjected to fishing with muro ami. Live coral cover was approximately 29% for Seiinog and 27% for Hulao-hulao. Selinog reef is bordered by “‘dropoffs” at certain points; in contrast, Hulao-hulao is generally flat. ’ The income of the 120 Selinog fishermen, who fished for cash, was variable, ranging from PO,13 to P35.00 per man-hour. The value of the fish catch of the 60 Hulao-hulao’ fishermen, who fished only for home consumption, was much lower—about PO.12 to P13.71 per man-hour.